Transition of the GOCCs to the pivate enterprises effect on the government, GOCC itself, and to economic growth - Galang, Riza S.; Guanlao, Ma. Roschiel O.
Privatization process in the country has met some remarkable success in generating additional revenue for the government and even reducing the fiscal burden of public enterprises by transposing GOCCs to private firms. This is very much noticeable during the mid 90s wherein the country had experienced a fiscal surplus even just for a short period of time. The Philippine experience in privatization started with strong intentions. The sale of major assets at a fairly good price had demonstrated the maturity of Philippine capital markets, the capacity of its institutional and regulatory framework, the availability of technical expertise to undertake the preparation of privatization plans for specific assets and the existence of enough interested investors. However, the average rate of recovery in the disposal of non-performing assets of the government has been relatively low. In addition, most of the GOCCs that have been privatized and those subject to privatization are considered to be small-scale enterprises. Moreover, the impact of privatized firms has produced mixed results. Like for example, the cases of Philippine National Oil Company (PNOC) and Petron Corporation are considered to be success stories. While on the contrary, Metropolitan Waterworks and Sewerage System (MWSS) and Metro Manila Transit Corporation (MMTC) privatization failed. With this, the researchers recommend that the government must ensure the positive effect of privatization measure on GOCCs to avoid incurring losses with every transaction they engage into. Another is that the government must consider privatizing those major non-financial GOCCs that rely so much in the financial assistance given to them that in turn increases the expenditure of the government in the form of subsidy. And lastly learning from the failures that happened in the past will be a big help in the future success of the privatization policy in the country.